Attitudes to Exotic Parakeets: A Comparative Case Study and Citizen Science Review - Ian D. Rotherham; Miles J. Watchman (Diversity, 2025)
Invasive, non-native species are recognised as a global problem, and their dispersal and introduction are controversial topics. However, a source of particular interest is that of human–nature interactions and consequent perceptions of natives and non-natives, an issue complicated by misunderstandings of history and sometimes of science. Furthermore, there are only few studies on the perceptions of exotic species by people living in a region subject to invasion. The research compared local stakeholder responses to a non-native invasive bird (ring-necked parakeet Psittacula krameri Scopoli) in two areas with contrasting scenarios regarding the history of establishment, their spread, and their current status. In both locations, parakeets were considered by respondents to be attractive, but where long-established, they were also viewed as a nuisance. Desire for or tolerance of active control measures also increased in areas with a well-established population in comparison to where parakeets were still viewed as a novelty. Increased encounters between native birds and invasive parakeets influenced attitudes towards possible controls. An online survey gathered stakeholder responses, and long-term citizen science and action research were combined with data from Local Environmental Records Centres and ornithological recording groups for each region.